Micromanufacturing Processes - Jain, V. K., editor 226634 (Boca Raton, FL : Taylor & Francis, 2013)
In addition to covering all processes in a single source, Micromanufacturing Processes also deals with various aspects of micromanufacturing. This book presents the principles, basic micro tools, and developments in micromanufacturing processes and systems. It also includes measurement techniques as well as research trends. Ideal as a reference for researchers or for undergraduate students, the text addresses several different types of micromanufacturing processes, such as micromachining, microforming, microcasting, microjoining, nanofinishing, and micrometrology. Figures and technical data illustrate the processes and concepts that are discussed by the author